Exploring distributed leadership in decision-making processes - Nor Azikin Mohd Omar
Despite the increased interest in an alternative constellation of leadership, scholarship dedicated to this intriguing area is still scarce, particularly from a qualitative research perspective. Moreover, much current leadership research still utilises rather 'less critical' functionalist and interpretive methodological tools such as questionnaires, surveys and interviews (Alvesson and Spicer, 2014). This study addresses these issues by taking a discourse analytical approach, providing insights into how participants challenge, negotiate and exert influence in the enactment of distributed leadership (henceforth DL) and the achievement of shared objectives. A particular focus is on how decisions and decision-making (henceforth DM) are constructed and negotiated. This research is situated within the tradition of social constructionism and analyses DL at the micro-level of interaction. Drawing on evidence of leadership from DM discussions that take place in team meetings and WhatsApp messages, the study shows that leadership roles are distributed among members of different positions, and all members contribute to and display leadership by enacting, negotiating and ratifying decisions in these different interactional contexts. Using various discourse strategies, all members take on leadership roles when and if they possess authority, knowledge or experience of the issues raised. It could therefore be suggested that the various processes of DM talk that these members are engaging in are reflections of the DL practices observed in the team and thus constitutive of their acceptable workplace norms. This thesis contributes to the existing scholarship on two levels; theoretically and methodologically. Theoretically, it illuminates the significance of legitimising leadership attempts made by ordinary members, and methodologically, it contributes to the examination of leadership in virtual contexts. It is hoped that the empirical evidence provided in this study thereby mediate the current theorisations of leadership.